Local governmental management of discretionary and specific accruals - Pilcher, Robyn (Inderscience Publishers, 2011)
Introduction of greater private sector-inspired practices during the past several decades has had Australian local government struggling to produce satisfactory figures for myriad stakeholders. Now, more than ever, motivation exists for local government to manipulate accounting numbers. A prime objective of this study is to shed further light on earnings management within the public sector by analysing managerial discretion practices over accruals for local governments in Australia’s largest state, New South Wales, for the period from 2003/04 to 2005/06. Another unique contribution is that the study provides further evidence on the much under-researched area of specific accruals. Discretionary accruals are calculated using the Jones model, whereas unexpected specific accruals are measured using modified approaches of Marquardt and Wiedman. Findings provide support for the view that different political, commercial and social pressures based on the local government size and locality lead different users of specific accrual accounts to manage earnings.